Premature Ventricular Contraction Classification Using Wavelet Features And Probabilistic Neural Network - Amir Hamzah, Nur Asyiqin (2010)
Electrocardiogram (ECG) classification is vital in determining the health condition of an individual. Cardiologist examine ECG as a means of detecting heart condition and dangerous heart condition. Particularly, accurate detection of Premature Ventricular Contraction (PVC) is essential to prepare for the possible inception of life threatening arrhythmia.